Correlating the morphology of Anacardium occidentale L. fruits from 30 orchards with their physicochemical and nutritional properties - Dakuyo, Roger; Konaté, Kiessoun; Bazié, David; Sanou, Abdoudramane; Kaboré, Kabakdé; Sama, Hemayoro; Santara, Balmoussa; Konkobo, Frédéric Anderson; Dicko, Mamoudou Hama (Frontiers in Plant Science, 2022)
Cashew (Anacardium occidentale L.) is a cross-pollinating plant whose fruit consists of two parts, the nut, and the apple. This study aimed to carry out agro-morphological characteristics of cashew fruits to establish relationships with their physicochemical and nutritional properties. Thirty (30) cashew accessions fruits were sampled in different regions of Burkina Faso. The length, width, thickness, weight, yield, kernel output ratio (KOR), proximate composition, specific minerals, phenolic compounds, and anti-nutritional factors were assessed. Evaluations were made using standard methods. The results showed significant variations in agro-morphological, physicochemical and nutritional traits depending on the accessions and the organ. Also, the ratio of apple mass versus nut one was about 12.24 ± 1.24. Kernels are an important source of proteins, fat, total phenolic compounds, and flavonoids, with average contents of 22.84 ± 1.25 g/100 g, 51.65 ± 2.54 g/100 g, 9.78 ± 2.15 mg GAE/g, and 6.24 ± 12.15 mg QE/g, respectively. As for the apples, they contained substantial quantities of Potassium, Phosphorus, Chlorine, and Magnesium with contents of 611.24 ± 14.5 mg/100 g, 418.24 ± 16.47 mg/100 g, 332.24 ± 10.54 mg/100 g, and 224.95 ± 13.15 mg/100 g, respectively. Statistical analyses showed that mineral and phytate contents were positively correlated to cashew apples while phenolic compounds and tannins were strongly correlated with walnuts. Principal component analyses showed three groups of accessions based on apples and kernels characteristics. These data showed a direct relationship between cashew physicochemical, nutritional potentials, kernels, and apples’ agro-morphological characteristics. These data constitute an important basis for the identification of cashew accessions with high nutritional and economic potential.